The Synthesis of Hexaphenylcyclotriphosphazene in Improved Yield - Aslan, F.; Arslan, M. (Taylor & Francis Ltd, 2008)
The reaction between phenylmagnesium bromide and hexachlorocyclotriphophazene (N3P3Cl6) ( 1) was reinvestigated for the synthesis of hexaphenylcyclotriphosphazene (N3P3Ph6) ( 2) in high yield. The reaction is complete within two weeks at room temperature using toluene as solvent. When the reactants (PhMgBr and N3P3Cl6) were employed in a 6: 1, 36: 1 and 72: 1 molar ratio, compound 2 was obtained in 2.6%, 14%, and 33.4% yield, respectively. The formation of N3P3Cl6 ( 2) during the reaction was followed by thin-layer chromatography. Compound 2 was characterized by elemental analysis, IR, UV-VIS, H-1, C-13, and P-31 NMR spectroscopy as well as by mass spectrometry.
Keywords: Arylcyclotriphosphazene; cyclotriphosphazenes; hexachlorocyclotriphosphazene; hexaphenylcyclotriphosphazene; phosphazenes